2001
DOI: 10.1074/jbc.m103826200
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation of Peroxisome Proliferator-activated Receptor α Is Associated with Contractile Dysfunction in Hypertrophied Rat Heart

Abstract: In pressure overload-induced hypertrophy, the heart increases its reliance on glucose as a fuel while decreasing fatty acid oxidation. A key regulator of this substrate switching in the hypertrophied heart is peroxisome proliferator-activated receptor ␣ (PPAR␣). We tested the hypothesis that down-regulation of PPAR␣ is an essential component of cardiac hypertrophy at the levels of increased mass, gene expression, and metabolism by pharmacologically reactivating PPAR␣. Pressure overload (induced by constriction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
175
2
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 237 publications
(186 citation statements)
references
References 32 publications
8
175
2
1
Order By: Relevance
“…Finck et al (11) showed that selective overexpression of PPAR-␣ in heart caused ventricular hypertrophy and systolic dysfunction. Young et al (37) showed that PPAR-␣ mRNA levels decrease in the heart of mice subjected to pressure overload, suggesting that downregulation of PPAR-␣ is part of the adaptive response of the hypertrophic heart. Similar effects on PPAR-␣ expression were observed in the CnA transgenic mice (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Finck et al (11) showed that selective overexpression of PPAR-␣ in heart caused ventricular hypertrophy and systolic dysfunction. Young et al (37) showed that PPAR-␣ mRNA levels decrease in the heart of mice subjected to pressure overload, suggesting that downregulation of PPAR-␣ is part of the adaptive response of the hypertrophic heart. Similar effects on PPAR-␣ expression were observed in the CnA transgenic mice (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies showed that increased PPAR-␣ activity in heart can cause cardiomyopathy (11,37). Finck et al (11) showed that selective overexpression of PPAR-␣ in heart caused ventricular hypertrophy and systolic dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even though studies show mixed results [5,6], it is generally felt that the heart switches to a reliance on glycolysis as the primary pathway for energy production during the development of heart failure [7]. In the case of pressure 20 overload there is an increase in cardiac mass, re-expression of fetal genes, a suppression of genes related to several rate-limiting enzymes in fatty acid oxidation, enhancement of genes related to rate-limiting enzyme for glucose oxidation, and increased reliance on carbohydrate oxidation to enable maintenance of contractile function [8,9]. Also, an increased adrenergic tone in the setting of heart failure not only exerts a direct toxic effect on the myocyte [10] but also causes unfavorable changes in myocardial 25 energy use [11].…”
Section: Introductionmentioning
confidence: 99%